PERBANDINGAN ANTARA DUA PENDEKATAN NORMALISASI DATA HINGGA KONDISI FOURTH NORMAL FORM (4NF) - Michael Iskandar (Bina Ekonomi, 2003)
Data normalization is a technique used to create databases that are able to store data in an effective and efficient manner. This, in turn, will ensure the integrity of the data contained within those databases. The process of normalizing a database from completely unnormalized to its ultimate form is a gradual one, and in practical terms this is commonly thought of as necessitating at least four steps, each of which is marked with a specific "normalized form", usually annotated as 1NF, 2NF, 3NF, and 4NF. This paper compares two different approaches to achieve 4NF. The first method comprises the four steps usually described in books and articles, while the second approach needs only two-and-a-half of those steps to attain 4NF.